2006
DOI: 10.3892/ijo.29.4.889
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of p73 N-terminal isoform expression and p53 status have prognostic value in gynecological cancers

Abstract: Abstract. The goal of this study was to determine whether patterns of expression profiles of p73 isoforms and of p53 mutational status are useful combinatorial biomarkers for predicting outcome in a gynecological cancer cohort. This is the first such study using matched tumor/normal tissue pairs from each patient. The median follow-up was over two years. The expression of all 5 N-terminal isoforms (TAp73, ΔNp73, ΔN'p73, Ex2p73 and Ex2/3p73) was measured by real-time RT-PCR and p53 status was analyzed by immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Recent data appear to suggest a prognostic relevance for p73 expression in EOC [172,173]. For instance, Nivazi et al [172] found a significant correlation between high-p73 expression and poor survival in patients with this malignancy.…”
Section: P53mentioning
confidence: 96%
“…Recent data appear to suggest a prognostic relevance for p73 expression in EOC [172,173]. For instance, Nivazi et al [172] found a significant correlation between high-p73 expression and poor survival in patients with this malignancy.…”
Section: P53mentioning
confidence: 96%
“…More importantly, DN‐p73 is overexpressed in several tumors, among them breast [152], ovary [158,159], prostate cancers [160], melanoma [161], neuroblastoma [162] and hepatocellular carcinoma [163,164] and in most cases, DN‐p73 expression is associated with therapy failure, chemoresistance, metastasis and vascular invasion [165]. In melanoma xenografts DNp73 expression is associated with upregulation of Slug, downregulation of the actin binding protein EPLIN, activation of the IGF1R‐AKT/STAT3 pathway, loss of E‐cadherin and a higher ability to invade and metastasize [166].…”
Section: Dn‐p73s As a Proto‐oncogenementioning
confidence: 99%
“…Several studies have reported the expression status of TP73 isoforms in human tumors (18)(19)(20)(21)(22), but only a few showed the involvement of DTAp73 isoforms in the prognosis of patients (23)(24)(25)(26)(27)(28)(29)(30)(31). The failure or lack of tumor response is mainly due to drug resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%